(untitled) (ModaPalavra e-periódico, 2015)
The intent of this article is to investigate the changes of costumes over the centuries and its main theoretical perspectives that guide the studies on clothing and fashion. It also seeks to understand the terms that determine the field through study of etymological definition. As well, studies the garments from social, cultural and behavioral theories.